The Determinants and Valuation of Owabong Waterpark Tourist Destination - Agus Arifin; Rakhmat Priyono (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
This research analyzes the the economic valuation of Owabong development which focuses on two objectives, namely analyzing the determinants of tourist visits to Owabong using travel cost method and multiple regression technique, and determining willingness to pay of Owabong tourists using contingent valuation method. It is quantitative research where by using incidental sampling technique the primary data were collected from 96 respondents—tourists—and completed by secondary data from relevan institutions. The results are that (1) the variables that determine the number of visits to Owabong are travel costs, individual visitor income, and visitor perceptions of the facilities at Owabong; (2) willingness to pay (WTP) for Owabong visitors on weekdays can be a recommendation for entrance ticket increase of 20 percent, that is IDR30,000, while on weekends visitors don't want an increase in entrance ticket, which is still IDR35,000.